An Ensemble Learning Strategy for Panel Time Series Forecasting of Excess Mortality During the COVID-19 Pandemic - Ashofteh, Afshin (2022)
Ashofteh, A., Bravo, J. M., & Ayuso, M. (2022). An Ensemble Learning Strategy for Panel Time Series Forecasting of Excess Mortality During the COVID-19 Pandemic. Applied Soft Computing, 128(October), 1-17. [109422]. https://doi.org/10.2139/ssrn.4057314, https://doi.org/10.1016/j.asoc.2022.109422 ----- Fundinhg: The authors are grateful to the anonymous reviewers for their constructive comments. Afshin Ashofteh and Jorge M. Bravo were supported by Portuguese national science funds made available through the FCT under project UIDB/04152/2020-Centro de Investigação em Gestão de Informação (MagIC). Additionally, Mercedes Ayuso is grateful to the Spanish Ministry of Science and Innovation for funding received under grant PID2019-105986GB-C21 and to the Secretaria d’Universitats i Recerca del departament d’Empresa i Coneixement de la Generalitat de Catalunya for funding received under grant 2020-PANDE-00074 (research project directly related to COVID-19 and economy).